Radioactive iodine refractoriness in Middle Eastern differentiated thyroid cancer: clinical outcome and risk factor analysis - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Siraj, Nabil; Ahmed, Saeeda O.; Al-Rasheed, Maha; Qadri, Zeeshan; Siddiqui, Khawar; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2024)
Background: Radioactive iodine refractory differentiated thyroid cancer (RAIR-DTC) has received increasing attention due to its poor prognosis. However, outcomes may vary among patients with RAIR-DTC. The role of clinico-pathological and molecular prognostic factors in survival remains controversial, resulting in difficulty in selecting patients for new targeted therapies. We assessed mortality rate and DTC-specific survival in Middle Eastern RAIR-DTC to identify prognostic factors associated with survival. Methods: This single center, retrospective study enrolled 268 patients with RAIR-DTC. Mortality rate and DTC-specific survival were analyzed to identify prognostic factors related to survival. Univariate and multivariate analysis were performed using Cox proportional hazards model. Results: Of the 268 cases of RAIR-DTC, 40.3% (108/268) had absent 131I uptake (either on diagnostic or post-therapy whole body scan), 15.3% (41/268) had progressive disease (PD) despite 131 I, 7.5% (20/268) had persistent disease despite cumulative activity of I 131of >600 mCi and 36.9% (n=99/268) developed distant metastasis. On multivariate analysis, age (more than 45 years), presence of metastatic disease and tumors harboring telomerase reverse transcriptase (TERT) promoter mutations were independent prognostic factors for poor DTC-specific survival. Subjects were divided into 3 groups according to the number of risk factors; low risk (no risk factors); intermediate (≤ 2 risk factors); and high risk (all the 3 risk factors). Ten-year DTC-specific survival rates in low, intermediate and high-risk groups were 100.0%, 92.9% and 53.6%, respectively.The contribution of age greater than 45 years to RAIR-DTC mortality is impactful. Older age, presence of distant metastasis and TERT mutations could be used